The role of immunoglobulin in cerebrospinal fluid on the differential diagnosis of autoimmune encephalitis and viral encephalitis in children - Xiaolu Hu; Shen Cheng (BMC, 2024)
Abstract Background A case-control study was conducted to analyze the role of cerebrospinal fluid immunoglobulin in the differential diagnosis of autoimmune encephalitis and viral encephalitis in children. Methods One hundred and twenty patients with autoimmune encephalitis (AE) treated in our hospital from February 2021 to February 2022 were included as the observation group (AE group). 100 patients with viral encephalitis (VE group) were selected as the control group. The clinical data of all patients were collected and analyzed retrospectively. Immunoglobulin G (IgG) and immunoglobulin A (IgA)in cerebrospinal fluid of the two patients were measured by immune turbidimetry. Immunoglobulin M (IgM), and the diagnostic value of immunoglobulin in cerebrospinal fluid (CSF) in patients with AE was analyzed by receiver working curve (ROC). Results The level of IgG in the cerebrospinal fluid of the AE group was higher than that of the VE group, and the level of IgM was lower than that of the VE group, and the difference was statistically significant (P < 0.05). There was no significant difference in IgA levels between the two groups (P > 0.05). In terms of Magnetic Resonance (MR) features, the paraventricular, hippocampal, occipital and parietal lobes were more involved in AE patients, frontal and temporal lobes were more involved in VE patients, and paraventricular and occipital lobes were involved in MS. The proportion of bilateral extensive lesions in both groups was significantly higher than 50%. The proportions of patients in the AE group involving the lateral ventricle, insula, and parietal lobes were significantly higher than those in the VE group, and the proportions involving the basal ganglia, temporal lobes, and frontal lobes were significantly lower than those in the VE group, and the differences were statistically significant (All P < 0.05). The Area Under Curve (AUC) of IgG, IgA and IgM alone in the diagnosis of AE were 0.795(0.587-0.762), 0.602(0.502-0.631) and 0.627(0.534-0.708), respectively with the sensitivity values of 81.24% and 65.608, respectively and the specificity values of 65.08%, 57.54% and 75.01% respectively. The AUC of IgA + IgM in the diagnosis of AE was 0.733(0.617-0.849), and the sensitivity and specificity are 62.58% and 75.07% respectively. The AUC of IgA + IgG in the diagnosis of AE was 0.823(0.730-0.917), and the sensitivity and specificity were 81.24% and 67.54% respectively. The AUC of IgG + IgM in the diagnosis of AE was 0.886(0.814 ~ 0.958), and the sensitivity and specificity were 84.48% and 77.59% respectively. The AUC of IgA + IgM + IgG in the diagnosis of AE was 0.924 (0.868-0.981) with the sensitivity of 93.82%, and the specificity of 77.56%. Conclusion The level of immunoglobulin in cerebrospinal fluid can be used as an effective reference index for the diagnosis of AE. The combined detection of IgA, IgM and IgG can improve the accuracy, sensitivity and specificity of AE.